Perfil del estilo de vida en estudiantes de una Universidad Pública - Sergio Charry-Mendez; Esperanza Cabrera-Díaz (Universidad Francisco de Paula Santander, 2021)
Objective: Determine the lifestyle behaviors of first semester Public University Students. Materials and method: Quantitative, descriptive, cross-sectional research. The size of the sample consisted of 113 enrolled students for the 2020-1 semester. The instrument of struc-tured interview made by the Institutional Project Universidad Saludable was used. The data were worked using Excel and SPSS version 22, through an univariate descriptive statistical analysis of frequencies and contingency tables. Results: Most of the students do not do phys-ical exercise 70%, 51% do not do any physical activity, there is a high consumption of tobac-co and more than half are frequent consumers of alcohol, more than half show anguish and almost half show anxiety. Half of the students consider that the quality of their diet is bad and there is a low consumption of fruits. The consumption of added salt to food is mentioned by most students 82%. 28% are overweight or obese. Most do not know their levels of cholester-ol and triglycerides. There are no support networks of schoolmates and family in almost half of the students. Conclusions: It was found that the lifestyle profile of first semester students in a public university is characterized by sedentary lifestyle, frequent consumption of beer and cigarettes, bad nutrition, overweight and obesity, anguish, and anxiety